A mathematical model for evaluating the role of trypanocide treatment of cattle in the epidemiology and control of Trypanosoma brucei rhodesiense and T. b. gambiense sleeping sickness in Uganda. (May 2019) - Meisner, Julianne; Barnabas, Ruanne V.; Rabinowitz, Peter M.
Abstract: Background: Human and animal African trypanosomiases impose a large economic and health burden in their endemic regions. Large strides have been made in the control of human African trypanosomiasis (HAT), yet these efforts have largely focused on the non-zoonotic form of the disease. Using a mathematical model with a 10 year time horizon, we demonstrate the role of the cattle treatment with trypanocides in the epidemiology of zoonotic and non-zoonotic HAT in Uganda, and its potential implications on elimination and eradication of the disease. Methodology/principal findings: We created two compartmental, deterministic models, each comprised of three sub-models: humans, the tsetse fly vector ( Glossina fuscipes fuscipes ), and cattle. We applied these models to two HAT foci in Uganda: the gambiense (chronic, non-zoonotic) form in the Northern Region, and the rhodesiense (acute, zoonotic) form in the Eastern Region. Parameters were derived from prior literature or assumed. In both foci we assumed G. fuscipes fuscipes expresses zoophilic biting behavior. With trypanocide treatment of cattle administered every 3 months, treatment in stage I (representing engagement in active or passive surveillance) had a larger impact on HAT burden than cattle treatment coverage. However increasing cattle treatment coverage allowed for further reduction in prevalence in both foci. Using these model parameters, our estimated R0 suggests humans cannot alone sustain the HAT epidemic in Uganda. Conclusions/significance: Even in the absence of zoonotic transmission, loss of a preferred tsetse host species can affect HAT risk. Thus One Health strategies which integrate HAT and animal African trypanosomiasis control may improve the timeliness and sustainability of gHAT and rHAT elimination and eradication in Uganda. Furthermore, such strategies reduce the burden of a high-morbidity livestock disease of economic importance. Graphical abstract: Modeled burden of human African trypanosomiasis in Uganda, under varying integrated control strategies (Tc : solid vs. dashed vs. dotted; AH : thin = 30%, bold = 50%). A mathematical model for evaluating the role of trypanocide treatment of cattle in the epidemiology and control of Trypanosoma brucei rhodesiense and T. b. gambiense sleeping sickness in Uganda.Unlabelled Image Highlights: The African trypanosomiases cause human and animal morbidity and mortality. Large-scale control efforts have reduced new human cases in recent decades. Elimination of the chronic form of the human disease has been targeted for 2020. Models suggest elimination requires control of non-human tsetse and trypanosome hosts.